Sensing and Liquid–Liquid Extraction of Dicarboxylates Using Dicopper Cryptates - La Cognata, Sonia (ACS Omega, 2020)
[Image: see text] We report the investigation of dicopper(II) bistren cryptate, containing naphthyl spacers between the tren subunits, as a receptor for polycarboxylates in neutral aqueous solution. An indicator displacement assay for dicarboxylates was also developed by mixing the azacryptate with the fluorescent indicator 5-carboxyfluorescein in a 50:1 molar ratio. Fluorimetric studies showed a significant restoration of fluorophore emission upon addition of fumarate anions followed by succinate and isophthalate. The introduction of hexyl chains on the naphthalene groups created a novel hydrophobic cage; the corresponding dicopper complex was investigated as an extractant for dicarboxylates from neutral water into dichloromethane. The liquid–liquid extraction of succinate—as a model anion—was successfully achieved by exploiting the high affinity of this anionic guest for the azacryptate cavity. Extraction was monitored through the changes in the UV–visible spectrum of the dicopper complex in dichloromethane and by measuring the residual concentration of succinate in the aqueous phase by HPLC-UV. The successful extraction was also confirmed by (1)H-NMR spectroscopy. Considering the relevance of polycarboxylates in biochemistry and in the environmental field, e.g., as waste products of industrial processes, our results open new perspectives for research in all contexts where recognition, sensing, or extraction of polycarboxylates is required.